THE INFLUENCE OF TRAINING AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. BANK SUMUT SYARIAH SUB-BRANCH KARYA MEDAN - Amelia S., Risky; Safrin, Feby Aulia (Transpublika Publisher, 2023)
This study aims to analyze the effects of training and work motivation on employee performance at PT Bank SUMUT Syariah Sub-Branch Karya Medan. The research method used is quantitative research with an associative approach. The population of this study consisted of 35 employees from PT Bank SUMUT Syariah Sub-Branch Karya Medan. Sampling was conducted using a saturated sample model. Data collection involved the use of primary data obtained through questionnaire distribution, as well as secondary data obtained through literature review. The results of the research indicate that the training variable has an insignificant effect, while motivation has a significant effect on employee performance. Both training and work motivation variables collectively influence employee performance, as evidenced by a strong relationship with an R value of 0.88 or 88%. The Adjusted R Square value reveals that the training and work motivation variables explain 63.1% of the performance variable, while the remaining percentage is influenced by other unexplained variables.